(untitled) (Revista de Psicología, 2019)
The aim of the present review is to know which are the principal features of personality that allow to predict the academic success and to identify the relation of the same ones with other such psychological variables as the intelligence, the interests, self-efficacy beliefs and the goals of performance. Specially there has been in use the model of five factors of personality since it is considered to be one of the most exhaustive explanations and with better perspectives for the measurement of the personality. Of the realized review it can be said that of five factors of personality, more consistently associated with the academic success it is the factor Conscientiousness. With regard to the remaining features of personality the association is less clear. It hopes that the contributed information helps investigators and professionals of the educational area when understands and to identify who is the psychological boss who facilitates the academic success. Some limitations are mentioned and they propose new directives.